IMPLEMENTATION OF BUREAUCRATIC REFORM IN DEVELOPMENT ADMINISTRATIVE BUREAU REGIONAL SECRETARIAT OF WEST KALIMANTAN PROVINCE - Khalid Fahrudi (JPASDEV : Journal of Public Administration and Sociology of Development, 2023)
Khalid Fahrudi. One of the main factors that play a role in the realization of Clean Government and Good Government is bureaucracy. This is a demand of the community so that the bureaucracy reforms itself, bureaucratic reform must lead to the satisfaction of bureaucratic services for the community. Referring to the Presidential Regulation of the Republic of Indonesia Number 81 of 2010 concerning the Grand Design of Bureaucratic Reform 2010 – 2025 where the West Kalimantan Provincial Government must be committed to implementing the bureaucratic reform process. The area of change in Human Resource Management is one of the focuses of the West Kalimantan Provincial Government in the implementation of bureaucratic reforms which of course are also carried out by regional work tools, including the Development Administration Bureau as a new work unit that was formed. Therefore, this study is intended to provide an overview of how the implementation of the Implementation of Bureaucratic Reform in the Development Administration Bureau of the Regional Secretariat of West Kalimantan Province, especially in the area of changes in Human Resource Management. This research uses a descriptive method with a qualitative approach. In the process of data collection as well as data triangulation the authors used the method of interviewing with several different groups of informants and documentation methods. The results of this study indicate that the lack of resources and limited authority makes the implementation of programs/implementation activities not optimal. The absence of SOP support means that implementers do not fully understand in detail how to implement good programs/activities, so that the implementation of bureaucratic reforms, especially in the area of human resource management, is on average only able to fulfill 58.8% of indicator.